(untitled) (Journal of Dhaka Medical College, 2015)
Background: The ideal method of varicocele treatment is a controversial issue. The present study was designed to compare the outcome of laparoscopic palomo and open inguinal varicocelectomy. Methods: The present quasi experimental study was conducted in the Department of Urology, Dhaka Medical College Hospital, Dhaka, between July 2010 and June 2012 to compare the outcome of open inguinal and laparoscopic Palomo approach of varicocelectomy. Purposively selected 50 patients were divided into equal two groups, Group A and Group B treated with open inguinal varicocelectomy and laparoscopic Palomo varicocelectomy respectively. Statistical analyses were done by using SPSS and p value <0.05 was considered as significant. Results: In the present study, mean age of the patients of Group A and Group B were 29.1 ± 2.0 and 28.9±1.5 years respectively. Among the patients of Group A developed neither hydroeele nor testicular atrophy, where as in patients of Group B 20% and 12% developed hydrocele and testicular atrophy respectively. The recurrence rate of varicocele was lower in the Group A than that in the Group B. The findings of semen analysis at 1st and 2nd follow up visits show that there was negligible improvement in semen quality in terms of sperm count, motility and morphology. Conclusion: Open inguinal varicocelectomy is better than laparoscopic palomo varicocelectomy. Although sooner return to work is achieved by laparoscopic varicocelectomy, complications are more frequent than the open inguinal method. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21527 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 156-162